Secular narrations and transdisciplinary knowledge - Hannoum, Abdelmajid, 1960- author.
1 online resource.
Keywords: "This book considers secularism and its narrative expressions. It shows how secularism is articulated, and transmitted ubiquitously within state institutions and outside of them. Abdelmajid Hannoum does this by dissecting, in a series of essays, a variety of narrative forms, interrogating modes of their constitution and production, the dynamics of their translatability, the politics of their use, the struggle over their status of truth, and the conditions that make secular narration so central to our existence. The book ranges from a medieval narrative of the secular to a modern narrative, to anthropological secularism and religious experiences, to narratives of translation produced by what the author calls translation ideology, to historical narratives regulated by archival power and state secrecy, to narratives of violence, to narratives of recollection, as well as narratives of silence. Particular attention is paid to postcolonial French contemporary cultures and politics. Transdisciplinary approaches are deployed to not only reframe old questions in new ways but to posit new questions out of old ones. In doing so this innovative work opens up fresh discursive possibilities that cross traditional disciplines. It will be of interest to scholars of anthropology, history, and beyond"--